2020
DOI: 10.3390/cells9040914
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation Alters the Secretome and Immunomodulatory Properties of Human Skin-Derived Precursor Cells

Abstract: Human skin-derived precursors (SKP) represent a group of somatic stem/precursor cells that reside in dermal skin throughout life that harbor clinical potential. SKP have a high self-renewal capacity, the ability to differentiate into multiple cell types and low immunogenicity, rendering them key candidates for allogeneic cell-based, off-the-shelf therapy. However, potential clinical application of allogeneic SKP requires that these cells retain their therapeutic properties under all circumstances and, in parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
1
8
0
1
Order By: Relevance
“…These genes are subsequently modulated by inflammation and seem to be involved in regulating the immunological fate of FSK-MSCs [ 32 , 33 , 34 , 35 ]. In line with these findings, we have previously shown that an inflammatory milieu has a significant impact on the molecular profile of skin-derived precursors [ 14 ] and adult-derived human liver stromal/stem/progenitor cells [ 63 ]. These immunological changes need to be further characterized to guarantee a safe cellular product with consistent quality and high therapeutic efficacy [ 55 ].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…These genes are subsequently modulated by inflammation and seem to be involved in regulating the immunological fate of FSK-MSCs [ 32 , 33 , 34 , 35 ]. In line with these findings, we have previously shown that an inflammatory milieu has a significant impact on the molecular profile of skin-derived precursors [ 14 ] and adult-derived human liver stromal/stem/progenitor cells [ 63 ]. These immunological changes need to be further characterized to guarantee a safe cellular product with consistent quality and high therapeutic efficacy [ 55 ].…”
Section: Discussionsupporting
confidence: 62%
“…Immunomodulation assays were performed as previously described [ 14 ]. Briefly, peripheral blood mononuclear cells (PBMC) were obtained by Ficoll-Hypaque gradient centrifugation of peripheral blood from healthy donors with informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…Altogether, our data showed that ADHLSC, like for Adipose tissue MSC and skin progenitors [ 56 , 57 ], is a responsive therapeutic unit that can sense specific signals related to injury and responds accordingly. Thus, 9 day-sustained inflammatory environment negatively affected ADHLSC viability without impacting the potential of surviving cells’ hepatocytic differentiation.…”
Section: Discussionmentioning
confidence: 96%
“…Previous study had shown that proinflammatory cytokine cocktail (IFNγ, IL-1β, TNFα and IFNα) activated human skin-derived precursors displayed lesser efficacy compared to unstimulated counter parts in mitigating graft vs host response in an animal model ( 37 ). In contrast, a recent study has demonstrated that cytokine cocktail (IFNγ, IL-17, IL-1β, TNFα) stimulated human cord blood tissue derived MSCs (CBti MSCs) improved the outcome of xenogeneic mouse model of GvHD ( 38 ).…”
Section: Discussionmentioning
confidence: 99%